Circumstances for Committing Crimes in the Banking Sector: Normative and Legal Aspect - V. V. Korniienko (Bulletin of Kharkiv National University of Internal Affairs)
The historical way of the development of banking business and the state of its legislative provision, which had an impact on criminal behavior in this area, has been studied. It has been noticed that the responsible officials of banking institutions, due to their high level of education, skillfully used gaps or contradictions in the legislation for the useful purposes of illegal enrichment. They quickly adapt to amendments in normative and legal regulation and invent new schemes of criminal technology.